2019
DOI: 10.1038/s41467-019-13608-1
|View full text |Cite
|
Sign up to set email alerts
|

PBRM1 acts as a p53 lysine-acetylation reader to suppress renal tumor growth

Abstract: p53 acetylation is indispensable for its transcriptional activity and tumor suppressive function. However, the identity of reader protein(s) for p53 acetylation remains elusive. PBRM1, the second most highly mutated tumor suppressor gene in kidney cancer, encodes PBRM1. Here, we identify PBRM1 as a reader for p53 acetylation on lysine 382 (K382Ac) through its bromodomain 4 (BD4). Notably, mutations on key residues of BD4 disrupt recognition of p53 K382Ac. The mutation in BD4 also reduces p53 binding to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…P53 research has caught much attention in oncology, including kidney cancer. Although VHL is the most critical mutation in kidney cancer, p53 still has a vital role in the tumorigenesis of kidney cancer 37 . Some studies indicate that p53 is highly expressed in kidney cancer tissues, indicating that p53 may have a cancer-promoting effect on kidney cancer 11,38 .…”
Section: Discussionmentioning
confidence: 99%
“…P53 research has caught much attention in oncology, including kidney cancer. Although VHL is the most critical mutation in kidney cancer, p53 still has a vital role in the tumorigenesis of kidney cancer 37 . Some studies indicate that p53 is highly expressed in kidney cancer tissues, indicating that p53 may have a cancer-promoting effect on kidney cancer 11,38 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that ccRCC may be unique compared with other cancers with respect to TME modulation and immunotherapy response, and that immunosuppression from PBRM1 loss is unique to ccRCC. PBRM1 has been shown to have pleiotropic effects at a molecular level, including the recognition of acetylated histones and p53, while different bromodomains can either enhance or attenuate nucleosome interaction 55,56 . Tissue specific cells are programmed to express a set of genes unique to that cell type, and each tumor type has additional canonical mutations specific to that tumor.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that magnolol and MM1 enhanced p21 expression by inducing histone acetylation, thereby inhibiting cyclin D1 and CDK4 activities, as well as cell cycle progression. Additionally, magnolol and MM1 also induce p53 protein acetylation, which not only enhances its stability but also improves its ability to bind to the target gene promoter, thereby upregulating the expression of downstream tumor-suppressor genes such as p21 and BAX (58). These results indicated that magnolol and MM1 could regulate p21 expression via both direct and indirect pathways and consequently inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 94%